Paving the road from transport models to “new mobilities” models - Wind, Simon; Jensen, Ole B.; Kaplan, Sigal; Prato, Carlo (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
For half a century, tremendous efforts have been invested in developing transport models as a decision aid for policy makers in designing effective policy interventions and deciding among costly public projects for the benefit of the population. Transport and activity-based models are often criticized for neglecting the “new mobilities” turn (Urry 2007, Cresswell 2006), namely multiple mobility aspects and rationales, including social, cultural, material, aesthetic and affective, in analyzing travel behavior. This paper aims at taking a tentative first step in bridging the gap between the traditional transport modeling approach and “new mobilities” research by suggesting a model framework that considers non-instrumental transport rationales, personal latent traits and intra-household decision dynamics.